The Analysis idiom in Nadin Amizah’s “Bertaut” song lyrics. - Jasmine, Shoofy; Gorat, Lenny Marsella; Andreas, Andreas; Purba, Ina; Nasution, Muhammad Shofi; Putri, Dian Marisha (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2023)
This article presents and idiomatic analysis of the lyrics of Nadin Amizah, a talented Indonesian singer. The data collected was analyzed using qualitative methods, The data in this study were taken directly from Nadin Amizah's " Bertaut " Song lyrics. The article Begins by providing an overview of Nadin Amizah's highlighting and her use of posting storytelling and evocative imagery. It theb focuses on a line examination of the lyrics, identifying the idiomatic expressions employed and uncovering their underlying meanings. Thus, this research found 4 Simile Idiom in this research analysis that explained in the result and discussion part and this research also an correct the misunderstanding of the meaning of a song lyric that contains idioms so that the message in the song is conveyed correctly. Keywords : Nadin Amizah, Bertaut, Song Lyrics, idiomatic Expression, music analysis.